QUALITY IMPROVEMENT FOR THE PRODUCT GINGERBREAD, A STUDY REGARDING THE INFLUENCE OF DOUGH MATURATION TIME AND OF THE AERATION FORMULA ON THE PRODUCT’S TEXTURAL CHARACTERISTICS - Anca TULBURE; Cristina-Anca DANCIU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The processors’ disposition to satisfy the customers’ requirements is an essential quality management principle in the food industry. In view of offering a high-quality product to the consumer, various aspects related to the maturation time of gingerbread doughs obtained with various proportions of aeration agents (sodium bicarbonate and ammonium bicarbonate) and acidifier (sodium acid pyrophosphate) have been studied. One witness sample and 5 other samples were analysed. They were matured for 30, 60, 120, and respectively 150 minutes before the products thus obtained were processed and analysed. Maturation has a significant effect on the product’s resilience, which has led to an analysis of this aspect. Maturation influences the quality of the product but, at the same time, it impacts its price; it is important to allow the space needed to achieve maturation in the flow, to organise the process flow, and to observe the parameters which need to be attained and monitored.